Empowering Indonesian Vocational Students with Artificial Intelligence Awareness: Challenges and Career Opportunities - Suyahman, Suyahman; Prayitno, Kintung; Pratama, Genta; Biddinika, Muhammad Kunta; Yudhana, Anton (Journal of Social Sciences and Technology for Community Service (JSSTCS), 2024)
Artificial intelligence (AI) has emerged as one of the most transformative and influential technological advancements, significantly impacting sectors like healthcare, finance, and education in the rapidly evolving digital era. However, vocational high school students often have limited knowledge about AI, primarily due to the superficial coverage of AI in their curriculum and the lack of resources and trained educators. This study aimed to assess the effectiveness of an intervention designed to enhance AI awareness and understanding among vocational high school students. A comprehensive program was implemented, involving initial assessments, interactive face-to-face training sessions, and facilitated group discussions. Descriptive analysis using statistical methods was employed to compare pretest and posttest data, revealing significant improvements in students' knowledge and attitudes towards AI. For example, the average score for the question "I know what Artificial Intelligence is" increased from 1.77 to 2.93, while "I can name an example of an AI application" rose from 1.76 to 2.85. Additionally, students showed increased awareness of AI's impact on future careers and a greater interest in learning more about AI, with scores rising from 2.20 to 2.85 and 2.48 to 2.96, respectively. The intervention proved effective in significantly enhancing students' understanding and attitudes towards AI, highlighting the value of targeted educational programs. By addressing gaps in AI education and fostering a proactive learning environment, the approach equips students with the knowledge and skills necessary to thrive in an AI-driven job market. This comprehensive strategy not only prepares students for future career challenges but also empowers them to leverage AI technology for career advancement.